GAW20: Methods and strategies for the new frontiers of epigenetics and pharmacogenomics - Tintle, N.; Fardo, D.; De Andrade, M.; Aslibekyan, S.; Bailey, J.; Bermejo, J.; Cantor, R.; Ghosh, S.; Melton, Phillip; Wang, X.; MacCluer, J.; Almasy, L. (2018)
© 2018 The Author(s). GAW20 provided a platform for developing and evaluating statistical methods to analyze human lipid-related phenotypes, DNA methylation, and single-nucleotide markers in a study involving a pharmaceutical intervention. In this article, we present an overview of the data sets and the contributions analyzing these data. The data, donated by the Genetics of Lipid Lowering Drugs and Diet Network (GOLDN) investigators, included data from 188 families (N = 1105) which included genome-wide DNA methylation data before and after a 3-week treatment with fenofibrate, single-nucleotide polymorphisms, metabolic syndrome components before and after treatment, and a variety of covariates. The contributions from individual research groups were extensively discussed prior, during, and after the Workshop in groups based on discussion themes, before being submitted for publication.